PEMBERDAYAAN UMKM PONDOK HUSNIL MELALUI PEMBUKUAN DIGITAL BERBASIS APLIKASI MYBISNIS - Herlin Kartika Meganingrum; Husnil Khotimah; Fadlina Wirlanda; D Nurlatifah; Septi Ana Prihatini; Zara Tania Rahmadi; Indra Setiawan; Dias Adi Dharma (ASOSIASI IDEBAHASA KEPRI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) serve as a strategic pillar for the national economy through significant labor absorption and creative innovation. However, the operational sustainability of MSMEs is often hindered by conventional and non-standardized financial governance. This community service program aims to transform the accounting system of UMKM Pondok Husnil through the digitalization of bookkeeping based on the MyBisnis application. The study employs a Mixed Methods approach, encompassing digital literacy surveys, application introduction, intensive technical guidance, and on-site mentoring. The results demonstrate that the implementation of the MyBisnis application has a significant impact on improving the partner's managerial efficiency. Key achievements of this program include the successful transition from partial reporting to an integrated digital system, enhanced understanding of capital structures and operational expenses, and the minimization of manual calculation errors. This digitalization enables real-time monitoring of cash flow and inventory, ultimately strengthening the competitiveness and accountability of MSMEs in the era of technological disruption.